2019
DOI: 10.1002/solr.201900128
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Optical Properties of Already Crystalized Hybrid Perovskite

Abstract: The optical properties of halide perovskite are already tuned in the initial solution by choosing the preferred precursors. However, it is not obvious that the optical properties change following perovskite crystallization; moreover, the mechanism in this case is not clear. Herein, it is shown that the optical properties are not necessarily “fixed” following perovskite crystallization. The phenomenon using the halide exchange process in the solid phase of an already crystalized perovskite is demonstrated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Tuning the activation energy and potential barriers for halide mobility is yet another theoretical route . On the other hand, the halide motion enables postsynthesis recrystallization. , Moreover, some segregation processes that appear due to redox chemistry under light might be reversible in the darkness. , Similarly, photobrightening and degradation for some samples are reverted and photodarkening occurs; however, effectiveness of the repair process depends on the light intensity and existence of charge necessary to balance the photogenerated holes …”
Section: Introductionmentioning
confidence: 99%
“…Tuning the activation energy and potential barriers for halide mobility is yet another theoretical route . On the other hand, the halide motion enables postsynthesis recrystallization. , Moreover, some segregation processes that appear due to redox chemistry under light might be reversible in the darkness. , Similarly, photobrightening and degradation for some samples are reverted and photodarkening occurs; however, effectiveness of the repair process depends on the light intensity and existence of charge necessary to balance the photogenerated holes …”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, 1D-GIWAXS demonstrates an obvious increase in the normalized intensity close to 1.2 selectively for TEAI·FABr, HBAI·FABr, and THAI·FABr except the case of FABr, which underlies the fact that the fluorinated alkyl ammonium iodide (TEAI, HBAI, or THAI) is necessary to strengthen the crystal orientation during the surface-limited reconstruction, although the crystal reformation is initially derived by FABr. The perovskite reformed by only FABr particularly shows an unstable surface with a high microstrain (Figure S3) being attributed to defects and local strain from a partial crystal distortion by halide exchange during the surface reconstruction. Two-dimensional (2D)-GIWAXS measurements were performed to investigate the detailed crystallographic information using two different incidence angles of 0.15 and 0.5° for exploring the surface (4.3 nm deep) and the bulk (212 nm deep) (Figure S4). Figures S5 and S6 show 2D-GIWAXS patterns corresponding to the surface and the bulk of perovskite films, where the (001) ring shows a dominant orientation at a tilted angle (edge-on orientation), as shown in Figure S7 .…”
Section: Resultsmentioning
confidence: 99%
“…The HBAI·FABr in particular shows the most suppressed nonradiative recombination owing to the most preferentially developed crystal facet of (001) over (111), coupled with the passivation effect. In addition, the highest n value of 1.83 for the perovskite film treated with only FABr is assumed to be the unstable reconstructed surface owing to the hygroscopic nature of FABr and the use of a high concentration of FABr solution. , In parallel with the n value, the recombination resistance ( R rec ) was measured using impedance spectroscopy to investigate the effect of passivation salt on the recombination behavior at the interface. The measured Nyquist plots are shown in Figure S13 with fitted curves using an equivalent circuit.…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to the aforementioned results, some other studies indicated trigonal symmetry and tetragonal Bravais lattice for FAPbI 3. 62–64 A first‐principle calculation exhibits a trigonal structure with a P3m1 space group for FAPbI 3 17,57,63,65 …”
Section: Structural Propertiesmentioning
confidence: 99%